Antimicrobial‐Resistant E. coli from Surface Waters in Southwest Ontario Dairy Farms. Issue 5 (1st September 2018) - Taggar, Gurleen; Rehman, Muhammad Attiq; Yin, Xianhua; Lepp, Dion; Ziebell, Kim; Handyside, Patrick; Boerlin, Patrick; Diarra, Moussa Sory
Abstract : Untreated surface waters can be contaminated with a variety of bacteria, including Escherichia coli, some of which can be pathogenic for both humans and animals. Therefore, such waters need to be treated before their use in dairy operations to mitigate risks to dairy cow health and milk safety. To understand the molecular ecology of E. coli, this study aimed to assess antimicrobial resistance (AMR) in E. coli recovered from untreated surface water sources of dairy farms. Untreated surface water samples ( n = 240) from 15 dairy farms were collected and processed to isolate E. coli . A total of 234 E. coli isolates were obtained and further characterized for their serotypes and antimicrobial susceptibility. Of the 234 isolates, 71.4% were pan‐susceptible, 23.5% were resistant to one or two antimicrobial classes, and 5.1% were resistant to three or more antimicrobial classes. Whole genome sequence analysis of 11 selected multidrug‐resistant isolates revealed AMR genes including bla CMY‐2 and bla CTX‐M‐1 that confer resistance to the critically important extended‐spectrum cephalosporins, as well as a variety of plasmids (mainly of the IncF replicon type) and class 1 integrons. Phylogenetic and comparative genome analysis revealed a genetic relationship between some of the sequenced E. coli and Shiga toxin‐producing E. coli O157:H7 (STEC), which warrants further investigation. This study shows that untreated surface water sources contain antimicrobial‐resistant E. coli, which may serve as a reservoir of AMR that could be disseminated through horizontal gene transfer. This is another reason why effective water treatment before usage should be routinely done on dairy farm operations. Core Ideas: Surface water is a valuable input for livestock production. Untreated surface water can be a source of antimicrobial‐resistant bacteria. Multidrug‐resistant E. coli strains may facilitate spread of antimicrobial resistance (AMR). Whole genome sequencing provides insight into the molecular ecology of E. coli from surface water. This highlights the need to implement efficient water treatment units for dairy farms.